The Influence of Geomembrane Technology and Production Management on Salt Productivity and Its Implications for the Welfare of Salt Farmers in Madura - Sayyidi Sayyidi; Zaini Moh (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2026)
Salt production in Madura plays a strategic role in the regional economy but continues to face challenges of low productivity and limited farmer welfare. This study aims to analyze the influence of geomembrane technology and production management on salt productivity and its implications for the welfare of salt farmers. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Primary data were obtained through Likert-scale questionnaires distributed to 230 salt farmers across four districts of Madura—Bangkalan, Sampang, Pamekasan, and Sumenep—using a purposive sampling technique. The results show that geomembrane technology has a positive effect on both productivity and farmer welfare, while production management exerts a more dominant influence on salt productivity. Furthermore, productivity is proven to act as a mediating variable that links the influence of geomembrane technology and production management with farmer welfare. These findings emphasize the importance of integrating technological innovation with effective management practices as a strategy to strengthen the competitiveness of the local salt industry and to strengthen the economic resilience of coastal regions.